The Role of the Human Entorhinal Cortex in a Representational Account of Memory - Schultz, Heidrun; Sommer, Tobias; Peters, Jan (Frontiers in Human Neuroscience, 2015)
Connectivity studies in animals form the basis for a representational view of medial temporal lobe (MTL) subregions. In this view, distinct subfields of the entorhinal cortex (EC) relay object-related and spatial information from the perirhinal and parahippocampal cortices (PRC, PHC) to the hippocampus. Relatively recent advances in fMRI methodology allow examining properties of human EC subregions directly. Antero-lateral and posterior-medial EC subfields show remarkable consistency to their putative rodent and nonhuman primate homologues with regard to intra- and extra-MTL functional connectivity. Accordingly, there is now evidence for a dissociation of object-related vs. spatial processing in human EC subfields. Here, variance in localization may be integrated in the antero-lateral vs. posterior-medial distinction, but may additionally reflect process differences. Functional results in rodents further suggest material-specific representations may be more integrated in EC compared to PRC/PHC. In humans, however, evidence for such a dissociation between EC and PRC/PHC is lacking. Future research may elucidate on the unique contributions of human EC to memory, especially in light of its high degree of intrinsic and extrinsic connectivity. A thorough characterization of EC subfield function may not only advance our understanding of human memory, but also have important clinical implications.